2015
DOI: 10.1007/s10265-014-0698-z
|View full text |Cite
|
Sign up to set email alerts
|

Acclimations to light quality on plant and leaf level affect the vulnerability of pepper (Capsicum annuum L.) to water deficit

Abstract: We investigated the influence of light quality on the vulnerability of pepper plants to water deficit. For this purpose plants were cultivated either under compact fluorescence lamps (CFL) or light-emitting diodes (LED) providing similar photon fluence rates (95 µmol m(-2) s(-1)) but distinct light quality. CFL emit a wide-band spectrum with dominant peaks in the green and red spectral region, whereas LEDs offer narrow band spectra with dominant peaks at blue (445 nm) and red (665 nm) regions. After one-week a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
1
19
2
Order By: Relevance
“…Although effects of light quality on photosynthetic characteristics has been studied in various species of plants, effects of blue and red lights on photosynthetic electron transport capacity has rarely been further investigated (Hoffmann et al 2015;Li et al 2013;Matsuda et al 2007). In this study, red light severely injured electron transport from Table 3), accompanied by lower connectivity (positive L-band; Fig.…”
Section: Blue Light Benefits Photosynthetic Electron Transport Capacitymentioning
confidence: 74%
“…Although effects of light quality on photosynthetic characteristics has been studied in various species of plants, effects of blue and red lights on photosynthetic electron transport capacity has rarely been further investigated (Hoffmann et al 2015;Li et al 2013;Matsuda et al 2007). In this study, red light severely injured electron transport from Table 3), accompanied by lower connectivity (positive L-band; Fig.…”
Section: Blue Light Benefits Photosynthetic Electron Transport Capacitymentioning
confidence: 74%
“…Meanwhile, both Chls and Cars have low light absorption at 530-610 nm. Previous studies (Nhut et al, 2003;Lee et al, 2007;Johkan et al, 2010;Guo et al, 2011;Lin et al, 2011;Liu et al, 2011;Fan et al, 2013, Hoffmann et al, 2015Hoffmann et al, 2016) have demonstrated that blue light induced the synthesis of Chl and Car. In our study, the concentrations of Chl and Car were greater under FL, B, and RB treatments, with the exception of (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Light induces the Chl biosynthesis pathway, and different spectrums influence the formation of photosynthetic pigments (Jilani et al, 1996;Hoober et al, 1999;Su et al, 2014). Blue light induces higher Chl a/b ratios (Rivkin, 1989;Demarsac et al, 1993;Chen et al, 2014;Hoffmann et al, 2015) and greater accumulations of Chl (Kurilčik et al, 2008;Poudel et al, 2008;Hoffmann et al, 2016). Red light inhibits Chl synthesis at lower concentrations of Chl and precursors like 5-aminolevulinic acid (Tanaka et al, 1998;Sood et al, 2005), protoporphyrin IX (PPIX), magnesium protoporphyrin IX (MGPP), and protochlorophyllide (Pchlide) (Fan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, blue light causes changes in the composition of chloroplasts providing a higher Chl a / Chl b ratio [19]. Green radiation has a generally positive effect on the plant development [20].…”
Section: Test Results and Discussionmentioning
confidence: 99%